INFLUENCE OF ARGAN FRUIT PEEL ON THE QUALITY AND OXIDATIVE STABILITY OF ARGAN OIL AFTER PROLONGED STORAGE. - Harhar, Hicham; Gharby, Said; Bouzoubaa, Zakia; Kartaha, Badr Eddine; Charrouf, Zoubida; Guillaume, Dominique (Emirates Journal of Food and Agriculture, 2015)
The quality of argan oil produced from peeled- or unpeeled-fruit stored for up to two years was investigated. Key physicochemical parameters were periodically determined during the study: peroxide and acid value, specific extinction, fatty acid content, and tocopherol content. Since no significant differences were observed in the composition of argan oil prepared from fruit stored with or without peel over a two-year period, argan fruit peel does not influence the physicochemical properties of argan oil.